2005
DOI: 10.1038/sj.onc.1208816
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide upregulates the cyclooxygenase-2 expression through the cAMP-response element in its promoter in several cancer cell lines

Abstract: We previously showed that nitric oxide (NO) induces overexpression of cyclooxygenase-2 (COX-2) and production of prostaglandin E 2 in cancer cells. Here, we investigated the mechanisms by which NO induces COX-2 expression in cancer cells. We found that the cAMP-response element (CRE) is a critical factor in NOinduced COX-2 expression in all cells tested. We found that in cancer cells, three transcription factors (TFs) -cAMP response element-binding protein (CREB), activating transcription factor-2 (ATF-2) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 33 publications
0
33
0
1
Order By: Relevance
“…Expression of COX-2 is stimulated by NO through the cAMP-response element (14), and thus, the cytotoxicity of NO has been considered to be closely related to the action of increased prostaglandins resulting from the induction of COX-2 (10). Several lines of evidence showed that anti-inflammatory action of eugenol compounds depends on the inhibition of the COX-2 expression (6,13,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of COX-2 is stimulated by NO through the cAMP-response element (14), and thus, the cytotoxicity of NO has been considered to be closely related to the action of increased prostaglandins resulting from the induction of COX-2 (10). Several lines of evidence showed that anti-inflammatory action of eugenol compounds depends on the inhibition of the COX-2 expression (6,13,17).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclooxygenase (COX-2), the rate-limiting enzyme in the sytnthesis of prostanoids, is responsible for the development of inflammation, and its expression is dependent on the NO levels (14). Effect of eugenol compounds on the COX-2 expression was examined in the LPS-stimulated RAW264.7 cells.…”
Section: Effect Of Eugenol and Isoeugenol On Lps-induced Cox-2 Expresmentioning
confidence: 99%
“…In this regard, a recent study demonstrated that both DNA binding and transcriptional activation of NF-B began to rise in cultured myotubes after an 8-h incubation with palmitate (24). Moreover, p38 has been shown to directly regulate NF-B phosphorylation and its nuclear localization in cardiac myocytes (55), and direct involvement of the p38-ATF-2 pathway in the regulation of COX-2 expression has also been reported in other cell types (23,43). Supporting this notion is our observation that SB-203580 failed to reverse the IB degradation elicited by palmitate treatment (Fig.…”
Section: Palmitate-induced Cox-2 Expression Requires the Activities Omentioning
confidence: 99%
“…It has been also proposed that in macrophages the CRE site can be occupied by an AP-1 complex, as a cox-2 reporter could be repressed by a dominant negative c-jun construct (12). A role for c-jun in cox-2 induction has also been shown in other cell types (13,14). A recent study reporting a more detailed characterization of the mouse cox-2 promoter has helped resolve these issues.…”
mentioning
confidence: 96%